PENGEMBANGAN E-MODUL IPA TERPADU BERBASIS PROJECT BASED LEARNING MATERISTRUKTUR DAN FUNGSI JARINGAN TUMBUHAN KELAS VIII SMP - Eresti, Ages; Kasmantoni, Kasmantoni; Latipah, Nurlia (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2021)
E-modules are teaching materials that are considered innovative for learning. as an innovative teaching material, the e-module should be developed by the teacher himself to suit the character of the students and the learning methods to be used. the objectives of this study are four, namely: to find out how the level of needs analysis for the e-module science media as a medium for learning science material on the structure and function of plant tissue for class viii smp/mts, to find out how the prototype of the development of the e-module ipa as a medium for learning science material structure and the function of plant tissue for class viii smp/mts, to find out how the results of expert validation of the e-module science media as a science learning media material on the structure and function of plant tissue for class viii smp/mts, to find out how students respond to the e-module ipa as a medium learning science on the structure and function of plant tissue for class viii smp/mts, to find out how the e-module of science is suitable as a medium for learning science on the structure and function of plant tissue for class viii smp this research was conducted in a junior high school 6 bengkulu city in april 2021. the method used in this study was the research & development (r&d) method of development. validation carried out by material experts, linguists and media/design experts as well as validation by a science teacher showed that the product developed was very feasible to use. the results of this study indicate that the e-module is suitable for use in teaching and learning activities in schools.